Contributions of Women in the Economic and Social Life in the Era of the Message - Mhmood, Sajida Mohammed Zaki (Al-Adab Journal, 2022)
The study aims to demonstrate the impact of women in society. It also shows their important participation in historical events, especially concerning the economic and social aspects, in the light of the care of the Prophet's, peace be upon him, in her education, providing guidance and advice to women, as they are the mainstay of society. The study Highlights the fact that the noble hadiths of the Prophet constitute a rich historical material, especially in the economic and educational fields. Since the beginning of the first Islamic society, women were allowed to take a leading role in the nation, and to demonstrate their intellectual and scientific competencies. The study concludes that some of the social and economic events accompanying the Prophet's biography revealed that good family education is a solid foundation that helps in building the individual and society.